2022
DOI: 10.3390/ijms232314789
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cross-Linking Cations on In Vitro Biocompatibility of Apple Pectin Gel Beads

Abstract: The study aimed to compare the in vitro biocompatibility of pectin gels formed by different cross-linking cations. Hydrogel beads named CaPG, ZnPG, FePG, and AlPG were prepared from 4% solutions of apple pectin using ionotropic gelling with CaCl2, ZnCl2, FeCl3, and AlCl3, respectively. Cations influenced the gel strength of the wet gel beads in the following order (least strong) Ca2+ < Zn2+ < Fe3+~Al3+ (most strong). The swelling degree of the CaPG beads after 24 h of incubation in the RPMI-1640 medium w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…As shown by the initial screening, the type of cross-linking cation affects the adhesiveness of the pectin hydrogel. The type of cross-linking cation is well known to be a significant determinant of pectin gel stability [ 16 , 23 ], drug-releasing behavior [ 15 , 20 ], biocompatibility [ 24 ], and other functional properties [ 25 ]. Calcium ions are mainly used as a cross-linker to obtain ionotropic pectin hydrogels, however, Zn 2+ and Al 3+ ion cross-linking provides better control of stability and drug release rate than Ca 2+ [ 20 , 21 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown by the initial screening, the type of cross-linking cation affects the adhesiveness of the pectin hydrogel. The type of cross-linking cation is well known to be a significant determinant of pectin gel stability [ 16 , 23 ], drug-releasing behavior [ 15 , 20 ], biocompatibility [ 24 ], and other functional properties [ 25 ]. Calcium ions are mainly used as a cross-linker to obtain ionotropic pectin hydrogels, however, Zn 2+ and Al 3+ ion cross-linking provides better control of stability and drug release rate than Ca 2+ [ 20 , 21 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, we did not further consider the adhesiveness of these hydrogels due to their low biocompatibility. It was previously shown that Zn 2+ cross-linked hydrogel had a cytotoxic effect on leukocytes and fibroblasts, and Al 3+ cross-linked hydrogel enhanced the production of the inflammatory cytokine IL-1β [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies have previously explored pectin colloidal gels crosslinked with iron, and have demonstrated that this cation produces one of the most stable forms, when compared to other most commonly used gels such as copper and calcium [28,36]. In this case, it is believed, from the FTIR analysis, that oxidation produced a greater number of carboxyl groups that could potentially participate in the ionotropic gelation, but it is possible that the number of these extra groups was not sufficient to cause a significant difference in the degree of crosslinking, and thereby affect swelling.…”
Section: Swelling Degreementioning
confidence: 99%
“…Recently, our group showed that a hydrogel made of ionically cross-linked apple pectin adhered to rat intestinal serosa ex vivo with a strength that depended on the type of cross-linking cation [23]. However, the serosal adhesion and strength of the ionotropic pectin gel were found to decrease significantly after incubation in physiological media [23][24][25]. Improvement of adhesivity and strengthening of the pectin gel network appear to be necessary to obtain promising hydrogel adhesives to treat anastomotic leakage.…”
Section: Introductionmentioning
confidence: 99%